Fine‐structural variance of family 3 carbohydrate‐binding modules as extracellular biomass‐sensing components of Clostridium thermocellum anti‐σI factors. (1st February 2014) - Yaniv, Oren; Fichman, Galit; Borovok, Ilya; Shoham, Yuval; Bayer, Edward A.; Lamed, Raphael; Shimon, Linda J. W.; Frolow, Felix
<x xml:space="preserve">Abstract</x> The anaerobic, thermophilic, cellulosome‐producing bacterium Clostridium thermocellum relies on a variety of carbohydrate‐active enzymes in order to efficiently break down complex carbohydrates into utilizable simple sugars. The regulation mechanism of the cellulosomal genes was unknown until recently, when genomic analysis revealed a set of putative operons in C. thermocellum that encode σI factors (i.e. alternative σ factors that control specialized regulon activation) and their cognate anti‐σI factor (RsgI). These putative anti‐σI‐factor proteins have modules that are believed to be carbohydrate sensors. Three of these modules were crystallized and their three‐dimensional structures were solved. The structures show a high overall degree of sequence and structural similarity to the cellulosomal family 3 carbohydrate‐binding modules (CBM3s). The structures of the three carbohydrate sensors (RsgI‐CBM3s) and a reference CBM3 are compared in the context of the structural determinants for the specificity of cellulose and complex carbohydrate binding. Fine structural variations among the RsgI‐CBM3s appear to result in alternative substrate preferences for each of the sensors.